The Implementation of a Primary HPV Self-Testing Cervical Screening Program in Malaysia through Program ROSE—Lessons Learnt and Moving Forward. - Woo, Yin Ling; Khoo, Su Pei; Gravitt, Patti; Hawkes, David; Rajasuriar, Reena; Saville, Marion (Current Oncology, 2022)
Program ROSE (removing obstacles to cervical screening) is a primary HPV-based cervical screening program that incorporates self-sampling and digital technology, ensuring that women are linked to care. It was developed based on the principles of design thinking in the context of Malaysia. The program illustrates the importance of collaborative partnerships and addressing the multi-faceted barriers from policy changes, and infrastructure readiness to the implementation of a radically new cervical screening program in communities. The paradigm shift in cervical cancer requires a monumental and concerted effort in educating both the healthcare providers and the general public. In this short review, we highlight how Pilot Project ROSE incorporated evidence-based tools that rapidly scaled up to Program ROSE. These ideas and solutions can be adapted and adopted by other countries. Notwithstanding the impact of COVID-19, it is incumbent on countries to pave the road towards the elimination of cervical cancer with pre-existing footpaths.